التعريف ببعض الأغذية التقليدية السورية التي يدخل فيها الحليب أو مشتقاته ودراسة بعض خصائصها الكيميائية والجرثومية 1. حلاوة الجبن - حرفوش, محسن (Latakia University Journal -Biological Sciences Series, 2017)
تم في هذه الدراسة التعرف على التركيب الكيميائي لحلاوة الجبن وخاصة محتواها من الدهن والبروتين, والمعادن بالإضافة إلى تقييم مدى توافر الاشتراطات الصحية من الناحيتين الكيميائية والجرثومية لعدة عينات منها مصنعة بطريقة تقليدية خلال عامي 2013 – 2014 من أربع مناطق مختلفة من الساحل السوري.أوضحت النتائج التباين الكبير في التركيب الكيميائي للعينات حيث تراوحت نسبة المادة الجافة بين 37.1% في اللاذقية و 42.4% في طرطوس ونسبة البروتين بين 9.8% في بانياس و11% في طرطوس. ولا يمكن بيان مدى مطابقة العينات للمواصفة القياسية السورية لأنها لم تحدد نسب المادة الجافة والبروتين, كما بينت هذه الدراسة أن حلاوة الجبن مصدر مهم للبروتين والدهن والمعادن والكربوهيدرات حيث كان المتوسط العام لهذه المكونات 10.3, 10.6, 4.4 و14.3% على التوالي. كما بينت الدراسة احتواء بعض العينات على نسبة من الرصاص أعلى من الحد المسموح به حسب المواصفة القياسية السورية (0.1مغ/كغ) حيث بلغت 0.17 مغ/كغ في إحدى عينات اللاذقية , كما بينت أيضاً تباين التعداد العام للبكتريا بين المناطق وكان أعلاها 1.81 x 105 في اللاذقية, بينما كانت في جبلة 1.81 x 104 وكان المتوسط العام أعلى مما حددته المواصفة القياسية السورية. كان عدد البكتريا المتبوغة اللاهوائية مرتفعاً في جميع العينات ما يدل على استخدام الحليب الخام ومشتقاته في عملية التصنيع وكانت جميع العينات سلبية لوجود بكتريا القولون والـE.coli والـ Staphylococcus aureus.In this study, the chemical composition of cheese dessert was performed, especially its content of fat, protein , and minerals, in addition to the health requirements of both chemical and microbial sides. Several samples manufactured in a traditional way during the years 2013 & 2014 from four different regions of the Syrian coast were analyzed. The results showed large variation in the chemical composition of the samples where the proportion of dry matter ranged between 37.1 % in Latakia and 42.4 % in Tartous; the protein content between 9.8% in Banias and 11 % in Tartous. the study showed that cheese dessert is an important source of protein , fat, minerals and carbohydrates , where the general average for these components was 10.3 , 10.6 , 4.4 and 14.3 %, respectively . The study showed that some samples contained a concentration of lead higher than the allowable limit by the Syrian standard specification ( 0.1 mg / kg ) , and reached 0.17 mg / kg in one of Latakia samples. The study also showed that the general count of bacteria varied between regions and was the highest 1.81x 105 in Latakia , while it was in Jabla1.81 x 104 , and the overall average was higher than the Syrian standard. The count of anaerobic bacteria was high in all samples indicating the use of raw milk or its derivatives in the manufacturing process. All samples were found negative for the presence of coliform and E.coli and Staphylococcus aureus.